"CORE POWER UNLEASHED: TRANSFORM YOUR PULMONARY HEALTH WITH ENHANCED VO2 AND FEV1" - Gowhar Ahmad Thokar; Professor Dharamveer Singh (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
In this study, 45 students from Government Higher Secondary School Barbugh Imamsahib in Shopian, India, were selected as subjects. They were divided into three groups of fifteen: a yogic practice group, a core strength group, and a combined training group. The variables chosen for this study were VO2max (maximum oxygen consumption) and FEV1 (forced expiratory volume in one second). The participants underwent a 12-week training program, conducted 4 days per week for 45 to 60 minutes per session, including appropriate warm-up and cool-down exercises. The criterion variables were assessed before and immediately after the training program. Data analysis was performed using ANCOVA (analysis of covariance), and Scheffé's post hoc test was applied to determine paired mean differences if the obtained F-ratio was significant. The level of significance was set at 0.05. The results indicated a significant difference among the experimental groups in the selected VO2max and FEV1 parameters.